2006
DOI: 10.3758/bf03192868
|View full text |Cite
|
Sign up to set email alerts
|

When more is less: Extending training of the blocking association following compound training attenuates the blocking effect

Abstract: Among the various phenomena reported in the associative-learning literature, few have encouraged as much research and development of new models as the blocking effect. In forward blocking (Kamin, 1968), responding to a target conditioned stimulus (CS), X, is impaired due to this CS's receiving pairings with an unconditioned stimulus (US) in compound with a second (blocking) CS, A, that was previously paired with the US on its own. Alternatively stated, the typical forward-blocking design consists of training w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
10
0
2

Year Published

2007
2007
2020
2020

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 28 publications
4
10
0
2
Order By: Relevance
“…Some have failed to observe blocking with only one Phase 2 training trial (Mackintosh, 1975b;Mackintosh, Dickinson, & Cotton, 1980) but other have observed blocking with a single compound trial (Balaz, Kasprow, & Miller, 1982). Azorlosa and Cicala (1988) (Pineño, Urushihara, Stout, Fuss, & Miller, 2006). Interestingly, the opposite of blocking, which is augmentation (Batsell & Batson, 2001), has also been investigated in terms of its dependency on the number of training trials.…”
Section: Other Variablesmentioning
confidence: 99%
“…Some have failed to observe blocking with only one Phase 2 training trial (Mackintosh, 1975b;Mackintosh, Dickinson, & Cotton, 1980) but other have observed blocking with a single compound trial (Balaz, Kasprow, & Miller, 1982). Azorlosa and Cicala (1988) (Pineño, Urushihara, Stout, Fuss, & Miller, 2006). Interestingly, the opposite of blocking, which is augmentation (Batsell & Batson, 2001), has also been investigated in terms of its dependency on the number of training trials.…”
Section: Other Variablesmentioning
confidence: 99%
“…Si bien los procedimientos pavlovianos se han usado ampliamente para dar cuenta de fenómenos cognitivos en humanos (p. ej., Didden et al, 2000;Livesey & Boakes, 2004;Melchers et al, 2008;Pineño et al, 2006), pocos estudios han utilizado este paradigma teórico y procedimental en el estudio de la formación de clases de estímulos.…”
Section: Discussionunclassified
“…ej., Blaisdell, Gunther & Miller, 1999;Mackintosh, 1975;McLaren & Mackintosh, 2000;Rescorla, 1999;Stout & Miller, 2007). Adicionalmente, variaciones de tipo procedimental relacionadas con el orden temporal y espacial de presentación de los estímulos, han permitido examinar las circunstancias bajo las cuales se dificulta el aprendizaje o la transferencia de funciones estimulativas tanto en animales (Pineño, Urushihara, Stout, Fuss & Miller, 2006) como en humanos (Livesey & Boakes, 2004;Rehfeldt, Dixon, Hayes & Steele, 1998;Singh & Solman, 1990).…”
Section: Unive R S I Ta S Psyc H O L O G I C Aunclassified
“…A second line of evidence arguing for common underlying learning mechanisms is provided by some recent studies (e.g., Denniston, Miller, & Matute, 1996; Miller & Matute, 1996; Pineño, Urushihara, & Miller, 2005; Pineño, Urushihara, Stout, Fuss, & Miller, 2006) demonstrating that backward blocking can be obtained with nonhuman subjects when the two training phases were embedded in what is normally the first phase of a sensory preconditioning procedure (Brogden, 1939), a type of higher-order conditioning. In a sensory preconditioning situation, the target CS is first paired with an innocuous stimulus (a surrogate outcome, S) rather than with a US.…”
mentioning
confidence: 99%